Analisis Akuntabilitas atas Pelaporan Penggunaan Dana Siap Pakai untuk Keperluan Penanggulangan Bencana Di Daerah - Intan, Intan; Antong, Antong; Junaidi, Junaidi (Universitas Muhammadiyah Metro, 2024)
This study explains how the Regional Disaster Management Agency (BPBD) in Palopo City implements performance accountability. The series of disasters experienced by Palopo City has raised public awareness of the vulnerability and vulnerabilities. The reactive approach and disaster management patterns are considered inadequate. A new, more proactive, comprehensive, and fundamental approach is needed to address disasters. Disaster management, as a comprehensive and proactive effort, begins with disaster risk reduction, emergency response, and rehabilitation and reconstruction. Furthermore, disaster management needs to provide information regarding its performance accountability to the public as a collaborative effort by stakeholders with complementary roles and functions, so that disaster management can become part of the development process that fosters disaster resilience.